SEJARAH TAFSIR MTA (MAJLIS TAFSIR AL-QUR'AN) - Asif, Muhammad (STAI AL-ANWAR SARANG, 2015)
Majelis Tafsir Al-Qur’an (MTA) recently claims that they don’t make exegesis of Al-Qur’an. But this opinion seems like different from the reality. It is fact that MTA has an exegesis book and continues to make exegesis of Al-Qur’an. This article describes the history of development and MTA exegesis dynamics. Since the exegesis was taught by the founder of MTA, Abdullah Thufail, MTA’s exegesis isn’t static. But has got many corrections, change, until revision. It is predicted that MTA’s exegesis is going to get development and continual. Key word: MTA, tafsir, revisi, berkelanjutan.